(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
The data about 116 species of lichenized and 10 species of lichenicolous fungi of arboretum F.E. Falz-Fein Biosphere Reserve of “Askania-Nova” are given. 81 from them are new for reserve, 10 – excluded from list of lichen biota of this territory. Caloplaca substerilis Vondrák, Palice & van den Boom, Lecania sylvestris (Arnold) Arnold, Marchandiomyces corallinus (Roberge) Diederich & D. Hawksw., Polychidium muscicola (Sw.) Gray, Scytinium callopismum (A. Massal.) Otalora, P.M. Jørg. & Wedin – are a new species for Ukraine, and Candelariella faginea Nimis, Poelt & Puntillo, C. subdeflexa (Nyl.) Lettau, Flavoplaca dichroa (Arup) Arup, Frödén & Søchting, Verrucaria breussii Diederich & Van den Boom. are new for plain part of Ukraine.